Grass that gets rid of salt - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
The normal way to reduce the salt content of saline. soils is to wash out the sodium with vast quantities of water. This however, can, damage the structure of the soil. To prevent this from happening, gypsum, (calcium sulphate), is used. Scientists...